The Obstacle of Female Heroism in Robert D. San Souci Mulan (Movie) as a Feminism Study - Transalia Mukti Nuswantari; Sugeng Purwanto (Dinamika Bahasa dan Budaya, 2021)
ABSTRACTThis writer's thesis discusses one of the elements of feminism, namely radical feminism in the Disney movie, Mulan employing Kate Millett's Theory, Sexual Politics (1970). This study uses a qualitative study as a reference in the preparation of research. Data collection was taken by watching movies, identifying data, and classifying data. Theanalysis is based on the statement of the problem.They are how Mulan's struggled to prove that a woman is also able to become a hero and What the factors that make Mulan unable to be a proud as a daughter in her family.Sexual politics is a belief that struggles for women to have masculine and feminine behaviors by fighting for gender equality so that actually women also need to do men's roles. of serving their husbands and caring for children, it is also considered that good women are only able to do. Besides that, Mulan wants to change the mindset of society if women can also do men's jobs. Women are able to fight if they have determination and courage. The purpose of the writer in writing this study is that readers who are currently studying feminism get a better idea of ​​the history of feminism especially radical feminism, and the writer also wants to invite readers to fight and struggle for women's rights in a good way, because society needs to understand equality, namely women's rights such as women's empowerment, etc.Keyword: Feminism, Radical Feminism, Patriarchy, Sexual Politic